The polymeric characteristics and photoluminescence mechanism in polymer carbon dots: A review. (December 2017) - Tao, Songyuan; Zhu, Shoujun; Feng, Tanglue; Xia, Chunlei; Song, Yubin; Yang, Bai
Abstract: A large amount of emerging research on carbon dots (CDs) has been gradually improving the understanding of their structures, properties and emission mechanism. Distinct from the dominating status of quantum confinement effect in quantum dots, CDs always suffer from the complicated optical properties, deriving from the large differences in raw materials and synthesis methods. The diverse concepts and species puzzle researchers and hinder the further study. Thus, there is an urgent need to unify the definition and clarify the confused relation of CDs. Herein, we classify the raw materials of CDs synthesis into small molecules and polymers, and discuss CDs from the aspects of raw materials. We believe that the polymer-like structures reserved in CDs are universal no matter from the condensation of small molecules or the direct inheritance of polymers. Moreover, many similarities are concluded between CDs and polymers through serious comparisons and enough evidences. The formation processes of CDs are mostly polymerization and the obtained CDs always possess polymeric characteristics, such as abundant reactive functional groups, polydispersity of products, highly crosslinked network structure and other similar properties to non-conjugated fluorescent polymers. Therefore, the new concept, polymer carbon dots (PCDs), is put forward to generalize all kinds of CDs based on the summary of related reports. Besides, the complicated influence factors of photoluminescence (PL) are discussed and mainly classified as molecule state, carbon core state, surface state and crosslink enhanced emission (CEE) effect. In general, this review puts forward PCDs as a unified definition of reported CDs, and summarizes the polymeric characteristics of PCDs from formation process and product properties, as well as simultaneously illustrates the PL mechanism. Highlights: Put forward a new concept as polymer carbon dots (PCDs) to unify the confused definitions of reported CDs. Summarize the polymeric characteristics of PCDs to offer a new angle to understand this luminescent material. Classify the PL mechanism as molecule state, carbon core state, surface state and crosslink enhanced emission effect. Pointed out the present challenges and provide with further research directions.